1998
DOI: 10.1099/0022-1317-79-3-565
|View full text |Cite
|
Sign up to set email alerts
|

The BglII-N fragment of herpes simplex virus type 2 contains a region responsible for resistance to antiviral effects of interferon.

Abstract: Double infection with two interferon (IFN)-sensitive strains of herpes simplex virus (HSV), HSV-1(17syn)and HSV-2(UW268), showed reduced inhibition of virus growth by IFN. Intertypic recombinants with IFN resistance were obtained from the doubly infected cultures. These results indicate that HSV IFN resistance is controlled by at least two genetic regions. Restriction endonuclease analysis demonstrated that the recombinants were similar to HSV-2 in their genomic structure but the BamHI-A, BglII-I and BglII-N f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The data in this study suggest that major determinants of corneal resistance to viral invasion are the IFNs, since KOS was capable of robust replication in corneas and ganglia of nonscarified IFNR −/− mice. This is consistent with the idea that different HSV strains may be differentially susceptible to the effects of IFNs ( 11 , 12 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data in this study suggest that major determinants of corneal resistance to viral invasion are the IFNs, since KOS was capable of robust replication in corneas and ganglia of nonscarified IFNR −/− mice. This is consistent with the idea that different HSV strains may be differentially susceptible to the effects of IFNs ( 11 , 12 ).…”
Section: Discussionsupporting
confidence: 90%
“…Only a few studies have examined a role for the host immune system in influencing the in vivo phenotypes of HSV strains and mutants. For example, infected cell protein (ICP)47 has been shown to influence neurovirulence by blocking CD8 + T cell responses, and certain large genomic fragments of HSV-1 and HSV-2 strains have been shown to confer resistance to IFNs, although specific genes have not been identified ( 5 , 11 , 12 ). This line of investigation is especially relevant to those viruses whose growth in culture is significantly reduced due to mutation of a transactivation function such as ICP0 ( 13 , 14 ), or a DNA replication function such as ribonucleotide reductase ( rr ) or thymidine kinase ( tk ), without which the virus cannot thrive in nondividing cells ( 15 , 16 ).…”
mentioning
confidence: 99%
“…Genetic studies have mapped IFN resistance to a 7.4-kb region of the HSV-2 genome that contains the vhs gene and portions of two flanking genes (35). Another genetic locus influencing HSV-2 resistance to IFN-␣/␤ has been mapped 60 kb distant from the vhs locus (51).…”
mentioning
confidence: 99%
“…4) HSV-1 ICP27 can decrease IFN-activated STAT1 phosphorylation and partially block STAT1 translocation to cell nuclei (Johnson and Knipe, 2010; Johnson et al, 2008). 5) The HSV encoded RNase, virion host shutoff (VHS) protein, degrades cellular transcripts and thereby prevents expression of IFN-associated antiviral genes (Chee and Roizman, 2004; Duerst and Morrison, 2004; Murphy et al, 2003; Narita et al, 1998; Su et al, 1993). Mutant viruses that specify deletions in these genes exhibit increased sensitivity to IFNs and are highly attenuated in mouse models (Duerst and Morrison, 2003; Halford et al, 2010; Korom et al, 2008; Leib et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Mutant viruses that specify deletions in these genes exhibit increased sensitivity to IFNs and are highly attenuated in mouse models (Duerst and Morrison, 2003; Halford et al, 2010; Korom et al, 2008; Leib et al, 1999). Although a paucity of direct mechanistic studies exist for HSV-2, genetic mapping and pathogenic studies have indicated that the HSV-2 VHS protein is vital for regulating type-I IFN responses, and therefore, deletion of VHS profoundly attenuates HSV-2 in vivo (Murphy et al, 2003; Narita et al, 1998; Su et al, 1993). …”
Section: Introductionmentioning
confidence: 99%